Interdiffusion in EuS -based epitaxial superlattice nanostructures - Fedorov, A.G.; Volobuev, V.V.; Samburskaya, T.V.; Sipatov, A.Yu. (Functional Materials, 2013)
The diffusion intermixing of layers during annealing of EuS -based epitaxial superlattice nanostructures was studied by X-ray diffraction technique. The interdiffusion coefficients for EuS —PbS , EuS —PbSe , EuS —SrS superlattices were determined basing on change of the intensity of near-Bragg reflection satellites in X-ray diffraction pattern. There are no layer intermixing in EuS —PbTe superlattice was observed.